Physiological adaptabillity, thyroid function, body composition and genetic variability in Central Asia high altitude populations - Pettener, D.; Facchini, F.; Luiselli, D.; Toselli, S.; Rimondi, A.; Ismagulova, A.; Sichimbaeva, K.; Ismagulov, O.; Fiori, G. (Acta Andina, 2025)
Data on physiological adaptability to high altitude, thyroid function, body composition and genetic variations were collected during the CAHAP (Central Asia High Altitude People) research program. More than 400 healthy adult males from four different populations were studied: a high altitude (HA) Kirghiz sample of the Sary Tash village in Pamir (3200 m); a reference Kirghiz sample from Talas (900 m); a middle altitude (MA) Kazakh sample from the Keghen valley (Tien Shan mountains, 2100 m) and a lowland (LA) Uighur population (600 m). Twenty physiological and somatometric characters are examined in the present report. There are significantly higher values of hemoglobin and erythrocytes in the mountain samples than in the lowland ones. The variations in lung volumes are controversial. No significant differences in thyroid function indicators (free T4 hormone and thyroid stimulating hormone) were noted between HA Kirghiz and LA Kirghiz. Results suggest the presence of physiological adaptations to hypobaric hypoxia in HA Kirghiz as well as in MA Kazakhs. The lower adiposity in MA Kazakhs than in the LA Uighurs seems to be related to stress connecte to the mountain environment as well as to the lifestyle. Total body water and extracellular body water, predicted by the dilution and bioelectric impedance methods, are highly correlated, suggesting the possibility of the reliable use of predictive formulae developed on Caucasian subjects. Blood group systems, isozymes and serum protein polymorphisms were anlayzed with multivariate methods. The genetic maps obtained using Principal Component analysis show the centrality of Uighurs, Kazakhs and Kirghiz within the wide genetic variability of Asian populations, in agreement with their geographic centrality and the complex history of the peopling of the region.